Dar es Salaam : histories from an emerging African metropolis - Brennan, James R.; Burton, Andrew (Andrew Ross); Lawi, Yusufu Qwaray (Book collections on Project MUSE., 2007)
From its modest beginnings in the mid-19th century, Dar es Salaam has grown to become one of sub-Saharan Africa's most important urban centres. A major political, economic and cultural hub, the city stood at the cutting edge of trends that transformed twentieth-century East Africa. Dar es Salaam has recently attracted the attention of a diverse, multi-disciplinary, range of scholars, making it currently one of the continent's most studied urban centres. This collection from eleven scholars from Africa, Europe, North America and Japan, draws on some of the best of this scholarship and offers a comprehensive, and accessible, survey of the city's development. The perspectives include history, musicology, ethnomusicology, culture including popular culture, land and urban economics. The opening chapter offers a comprehensive overview of the history of the city. Subsequent chapters examine Dar es Salaam's twentieth century experience through the prism of social change and the administrative repercussions of rapid urbanisation; and through popular culture and shifting social relations. The book will be of interest not only to the specialist in urban studies but also to the general reader with an interest in Dar es Salaam's environmental, social and cultural history.